Maintenance of recovery boilers from VLCC shipboard. Issue 1 (September 2020) - Faităr, C; Nedelcu, A; Buzbuchi, N; Stan, L; Dumitrache, C
Abstract: The integrated maintenance and diagnosis system is intended for the measurement, monitoring, diagnosis, prediction and analysis of the main technical and functional parameters of a mechanical plant for its safe operation. Various software versions are implemented on modern ships that can ensure constant and efficient surveillance of all systems. These integrated systems of maintenance can focus on a category of aggregates and can prevent a great part of the defects that result from the incorrect exploitation of the respective aggregate or the lack of ensuring an efficient maintenance process. Integrated automatic diagnostics systems for onboard installations are the most efficient means of operation used for a wide range of applications. Also, integrated systems for automatic fault diagnosis - ISAFD is intended for measuring, monitoring and analyzing the technical parameters of machines used in the energy, chemical, metallurgical, food, construction or naval.